Psychological factors of psychologist's personal brand promotion - DEMBYTSKA, Nataliia; PONOMARENKO, Ievgeniia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Nowadays psychologists are increasingly choosing the path of creating and promoting their own brand on social networks. And this applies to both beginners and professionals with many years of experience in running their own practice. On the one hand, this is caused by modern trends, market conditions and the digital transformation of the environment. On the other hand, a personal brand opens up wide opportunities for the realization of a psychologist's own ambitions: it is easier to conduct various kinds of researches, convey one's own expert opinion to the audience, organize and launch one's own trainings and other products. It is worth mention that the expansion of the audience also affects the number of clients and the psychologist's income. Therefore, building a personal brand is not only a path to popularity, but also an important form of self-realization. The purpose of the article is to highlight the results of a study of psychological factors in promoting a psychologist's personal brand on social networks.Methods. The self-worth diagnostic method (N. Mykolenko, B. Plekai), the method for determining the clarity of the self-concept (T. Campbell, adaptation of I. Shemelyuk), the method for assessing the level of tolerance for uncertainty (S. Badner, adaptation of G. Soldatova) and the Connor–Davidson resilience scale (CD-RISC-10, adaptation of Z. Kireeva, O. Odnostalko, B. Biron),  an author's questionnaire to study a psychologist's ability to effectively promote their own brand were used. The sample consisted of 62 psychologists (N = 62), of whom 58 were women and 4 were men. All participants participated in the survey voluntarily, with informed consent.Results. It was found that 18.0% of respondents have problems with self-worth. Among the most common problems are low self-acceptance and social alienation (10.0% each), which complicate the formation of a stable professional identity. 66.0% of respondents have a level of resilience above average, which indicates general emotional stability and the ability to adapt in conditions of stress or uncertainty. A relationship was found between the level of resilience and the level of income of specialists. The respondents have a predominantly average level of clarity of the self-concept, closer to high, which indicates the prevalence of this condition among the respondents. In 2.0% of respondents with an average level closer to low, the number of subscribers does not exceed 2 thousand, even with seven years of experience in managing social networks.Conclusions. The greatest influence on the promotion of a personal brand in social networks is exerted by self-worth, clarity of self-concept and resilience. Tolerance to uncertainty in itself is not decisive for achieving high results in the field of online promotion. Although it’s possible impact on the speed of promotion of a psychologist's personal brand in social networks is not excluded.
Keywords: personality; psychologist; personal brand; promotion in social networks; self-worth; clarity of self-concept; tolerance for uncertainty, resilience